Hakikat Keharaman Riba Dalam Islam - Khozainul Ulum (JES (Jurnal Ekonomi Syariah), 2016)
There is a negative assumption that arises in community with regard to economic transactions. For example, the statement "interest" and "profit-sharing" is similar, it justifies something that has become a previous habit. Whereas after having studied and researched, the economic transactions is belongings to the category of riba (usury) and society is still reluctant to get used to something right, which has not yet become a tradition. So, it is impressed that Islam does not take care of worship that do not directly relate to Allah, as obligatory (mahdoh) worship in the pillars of Islam. The question arising then is why the statement emerged from the realm of Muslims who are still reluctant to attempt to transact transactions that should be appraised with shariah paradigm? How is the danger of riba, in the world and the Hereafter? Author wants to convey thoughtfulness and perception related to economic thought developing at this time. They merely legitimize the phenomenon of conventional economics by attaching ayat and hadits although there are also alternative thoughts of genuine Islamic Economics, so easy to get caught up in usurious practice. Therefore, author is inspired to invite readers to dare to unburden, examine, and study riba (usury) and the reason of prohibition in Islam. The existence of incompatibility of Islamic economic theory with the application of contemporary economics does not mean that Islamic economics is not applicable, but it motivates us to implant Islamic economics proportionally and objectively in life. In order to analyze the problems, in this article, author uses a combination of mindset based on reality with faith, then author draws conclusion on the nature of reality of transaction, by  comparing reality with argument and opinion relating to" Does interest applied nowadays include riba and how is the danger of consuming usurious results?" Keyword: Riba, Interest, The danger of riba